Determinants of stock valuation: empirical evidence from Malaysia plantation companies - Cheng, Khai Ling (2018)
It is important for an investor to know a share’s value to slacken their chance of selling stocks ahead of time and missing out on future profits or buying a stock that priced too high for what it worth. Previous studies (Wilcox, 1984; Rappaport, 1986; Down, 1991) suggest that stock prices changes are connected with the variables that link with share valuation. In Malaysia, there have been no studies specifically related to the effects of stock value on planation companies listed at Kuala Lumpur Stock Exchange (KLSE). The present study analyses the share price performance of seven firms and seeks to identify the factors that influence share prices for the selected firms in various sectors at NSE by developing a model (s) for share price determination.